Survey of social wasps (Hymenoptera, Vespidae, Polistinae) in Amazon rainforest fragments in Acre, Brazil - Gomes, Bruno; Lima Knidel, Samilla Vanessa de; Moraes, Heroilson da Silva; Silva, Marjorie da [UNESP] (Inst Nacional Pesquisas Amazonia, 2018)
The State of Acre, in the southwestern Brazilian Amazon, harbors high biodiversity and a high degree of endemisms. Nevertheless, there are few studies on the diversity of social wasps occurring in this region. This study presents a list of social wasps (Hymenoptera, Vespidae, Polistinae) collected actively with attractive bait in three rainforest fragments in Acre. A total of 758 wasps belonging to 11 genera and 36 species were collected. Nineteen species were new distribution records for Acre and three others were new records for Brazil. Based on our results, further investigations should lead to a significant increase in Polistinae diversity in this region, producing information for biogeographic studies and management of natural areas.
Keywords: distribution records; Neotropical Region; swarm-founding wasps; Western Amazon